THE EFFECT OF FINANCIAL RATIOS AND LOCAL GOVERNMENT CHARACTERISTICS ON FINANCIAL DISTRESS CONDITIONS (Study on Local Governments of Districts / Cities throughout the island of Sumatra) - Wani Fitri; Muammar Khaddafi; Iswadi (CV. RADJA PUBLIKA, 2024)
This research aims to test the influence of financial ratios and local government characteristics on the financial distress conditions of District/City Local Governments across the island of Sumatra. The financial ratios utilized in this study consist of effectiveness ratio, efficiency ratio, growth ratio, and budgetary solvency ratio. Meanwhile, the local government characteristics include financial independence, population size, area size, and the degree of decentralization. The data used in this research are secondary data obtained from the Budget Realization Report (LRA) published by the Directorate General of Financial Balance (DJPK) of the Ministry of Finance. The data analysis technique employed is logistic regression analysis using Eviews version 10 software. The research results indicate that effectiveness ratio, efficiency ratio, budgetary solvency ratio, financial independence of the region, and the degree of decentralization have a negative influence on the financial distress conditions of local governments. However, growth ratio and population size do not affect the financial distress conditions of local governments. On the other hand, the area size has a positive influence on the financial distress conditions of local governments the island of Sumatra.